The Effect of William Flexion Exercise on Low Back Pain in Pottery Artisans - Maruli Taufandas; Anatun Aupia; Muh. Jumaidi Sapwal; Dina Alfiana Ikhwani; Nandang DD Khairari (Universitas Pendidikan Mandalika, 2025)
The activities performed by individuals continuously and the presence of heavy loads during physical activities can cause pain in the lower back. The occurrence of lower back pain can interfere with activities during daily work, the pain felt makes the sufferer uncomfortable in moving parts of the body, namely the back and waist areas. Researchers will answer the question,